Indian Thought, An Introduction - J B C (Journal of Dharma, 1976)
The great many and variety of introductions to Indian philosophy published recently in the West clearly indicate the felt need to inter- pret to the West "the wonder that was India"; The books under review is typical since it represents the major complementary approaches emphasising the distinctive character of Indian thought, the vicissitudes of historical development of a philosophical tradition or, rather, several traditions in juxtaposition, India's philosophical con- tribution to the perennial problems of human thought, and the depth of experience that lie behind its rational formulations.